A portable, remote‐controlled nest‐box trap. Issue 1 (8th February 2019) - Saunders, Cardy H.; Shutler, Dave
Abstract: Many researchers catch adult birds at nest boxes using a vertical prop that supports a horizontal flap that drops down when an adult enters to feed nestlings. Because the prop is visible, some birds may be too wary to enter nest boxes, or they may dislodge the prop when they lean in; either way, they are not captured. We describe a remote‐controlled nest‐box trap that has the advantages of portability and being invisible to adults delivering food to nestlings. A receiver is installed on the ceiling of a nest box, the receiver is connected to a spring‐loaded flap that is triggered remotely with a transmitter from > 30 m away, and the flap drops down to cover the box entrance. In 2017 and 2018, our remote‐controlled traps did not increase the likelihood of capturing female Tree Swallows ( Tachycineta bicolor ), but did improve the likelihood of capturing males. We captured 16 male Tree Swallows in 30 attempts (53.3%) using our remote‐controlled trap compared to only 41 captures of males in 139 attempts (29.5%) with prop traps. In addition, whereas prop traps required an average of ~ 50 min to capture adults in successful attempts, our trap required only ~ 25 min. These results suggest that the savings in time for field researchers using our remote‐controlled trap can be substantial, with the added ethical benefit of reducing the amount of time that nestlings are not being fed. Our remote‐controlled trap is also economical to construct, requiring ~ $60 USD for parts and < 3 h to build.